Core concepts in cultural anthropology - Lavenda, Robert H.; Schultz, Emily A. [ (Emily Ann)] , 1949- (McGraw-Hill, 2013)
Designed for courses that make extensive use of ethnographies and other supplementary readings, this is a concise, accurate introduction to the basic ideas and practices of contemporary cultural anthropology. Not a standard textbook, Core Concepts in Cultural Anthropology is more an annotated bibliography of the terms and concepts that anthropologists use in their work. The book prepares students to read ethnography more effectively and with greater understanding